Improvement in the mechanical strength of compacted urea fertilizer tablets through die wall lubrication - Shamsudin, Intan Soraya; Anuar, Mohd Shamsul; Yusof, Yus Aniza; Mohd Hanif, Ahmad Husni; Mohd Tahir, Suraya (Universiti Putra Malaysia Press, 2019)
This research was conducted to investigate the compaction performance and mechanical strength of compacted urea fertilizer in unlubricated and lubricated die systems. The ground urea 46% N fertilizer was compacted in a 13 mm flat-face cylindrical die set in both unlubricated and lubricated die systems with vegetable fatty acids and magnesium stearate as lubricants at various compaction stresses to produce urea fertilizer tablets. In conclusion, a lubricated die system reduces the frictional effects during the production of urea fertilizer tablets and also produces a mechanically stronger urea fertilizer tablet than those produced in an unlubricated die system. In addition, the vegetable fatty acids and magnesium stearate lubricants are found to improve the compaction performance of urea fertilizer tablet as well as its mechanical strength.